Вплив опору короткозамкненого витка на характеристики асинхронного двигуна з екранованими полюсами - Маляр, В. С.; Глухівський, Л. Й.; Гавдьо, І. Р.; Гречин, Д. П. (Видавництво Національного університету «Львівська політехніка», 2007)
The influence of resistance of short-circuited shading coil on the performance of shadedpole induction motors has been investigated. The electromagnetic parameters are calculated on the base of ramifided equivalent circuit of motor magnetic circuit.